UNEQUAL KNOWLEDGE PRODUCTION IN EU-SERBIA RELATIONS: A PROCESSUAL RELATIONAL ANALYSIS - Victor Jimenez Rivera, (PEOPLE: International Journal of Social Sciences, 2026)
The Jadar valley in Western Serbia is rich in jadarite, a unique lithium mineral making up 10 percent of global lithium ore reserves (Stefanović et al., 2023). Listed as a critical raw material for the EU's economy (Szlugaj & Radwanek-Bąk, 2022), lithium is a resource of increasing economic relevance, as it is key to automotive, electronics, energy, nuclear weapons, and other applications. Serbia is home to a unique source of this crucial resource, the extraction of which has been fraught with controversy due to the nature of the EU's involvement and the geoeconomic power relations surrounding global lithium markets, particularly due to the Anglo-Australian corporation Rio Tinto's centrality to the proposed jadarite mining project. The extraction of lithium in Serbia is reflective of unequal power dynamics and the securitization of critical raw materials. While Serbia is not an EU member state, it has close relations with the bloc due to its membership candidate status and its role as its near periphery. The paper argues that, while the EU and the Serbian government have framed lithium extraction as critical to fighting climate change and have highlighted potential for economic windfall for Serbia, the proposed project can nonetheless be best understood as critical to neocolonial resource extraction dynamics and geoconomic competition with rivals in global energy markets, particularly China. This reproduces green extractivist tendencies "saving global capital from its ecological contradictions" (Voskoboynik & Andreucci, 2022) and greening imperialism (Anlauf, 2016).The paper employs a relational approach to situating the proposed mining project in the aforementioned dynamics and understanding resistance to it among marginalized communities in Serbia as part of broader decolonial movements. The paper problematizes the establishment of a hegemonic narrative obfuscating the relational interplay between the actions undertaken by the Serbian government, the European Union, and the Rio Tinto corporation, as a tool in the legitimation of these processes in spite of the presence of a large protest movement and the displacement of marginalized communities that is at stake. Centering indigenous resistance, the protest movement is understood as an intersectional coalition and its resistance is framed as a crucial member in peripheral networks of solidarity, mutually constituting and informing their resistance to neocolonial resource extraction projects.